ChemInform Abstract: A Catalytic Enantioselective Tandem Allylation Strategy for Rapid Terpene Construction: Application to the Synthesis of Pumilaside Aglycon. Issue 30 (4th July 2013) - Ferris, Grace E.; Hong, Kai; Roundtree, Ian A.; Morken, James P.
Abstract Catalytic diboration of dienes followed by cascade allylborations with dicarbonyl compounds opens access towards terpenoid cyclohexane derivatives.